Decreasing Strength of Prestressed Concrete Beams Due to Failure of Part of the Strands Withdrawal - Budiadi, Andri (Jurnal Teknik Sipil dan Perencanaan, 2024)
Abstract.This research paper is to study the decreasing strength of a 22,1 meter long span Prestressed Concrete U Girder due to two strands in a tendon out of six tendon are not being able to be stressed. This matter is a cause of an error in the implementation of the PC-U girder manufacturing resulted in a reduction in the area of the tendon sleeve (duct), two out of seven pieces of the strand cannot be inserted completely. PC-U girder performance will suffer a strength decrease, it needs to be checked and handled.  This paper is an actual project condition and researched to verify how much strength reduction due to such a case.  Analysis is performed to measure and compare the moment capacity of a cross-sectional conditions in accordance with the results of the designed section. Moment capacity analysis is carried out to determine the ability of the cross section to support the working load with a bonded tendon. Research methodology involves calculation of moment capacity Mu using trial and error processes of calculating the depth of neutral axis c using Equilibrium Equation so that with a trial c value, ultimate prestressed strain value εpu and ultimate prestresses stress value σpu are coincided in the Moment-Curvature curve line. Using the overlapped c value, Moment capacity of the girder with full strand can be calculated. A similar procedure is performed with reduced strand number. The difference between the two are the reducing prestressed concrete strength. Evaluating both analyses, it is found that a decrease in the moment capacity of the cross section as much as 530,93 kNm to the designed moment capacity of 18.108,06 kNm or approximately 2,93% of its original designed strength.